PSYCHOLOGICAL FACTORS OF FINANCIAL RISKS MANAGEMENT OF BUDGETARY PROCESS - Elvira Rustamovna Mubarakshina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
In article such concepts are considered as the risk, budgetary risk, necessity of formation of system thinking at civil servants working in budgetary process. In article the concept of professional motivation for civil servants is considered. As in article necessity of the account of various psychological factors for managerial process by budgetary risks is proved and these factors are considered. In article risks in the field of public finances and a role of civil servants in the course of control over performance of the federal budget parameters and effective and target use of budgetary funds are considered. In article the urgency of the account of psychological factors at each stage of management by risks of budgetary process, in the answer constantly changing environmental conditions is proved. Aim: to reveal and characterize budgetary process risks.  Object of research: psychological factors of financial risks. Result: Substantiation of necessity of the account of psychological factors such as style of thinking, the person, professional motivation of the employee at revealing and the analysis of risks of budgetary process and decrease in influence degree of risks on budgetary process. DOI: http://dx.doi.org/10.12731/2218-7405-2013-7-37